Macy’s Latin American Fair: A Temple Built on the Anxieties of Inter/Americanism - Crossman, Lisa (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract In 1942, amidst an international crisis, Macy’s Department Store held a large-scale Latin American Fair in New York City. Through an analysis of the fair’s design, extensive art exhibition, and its coverage in the popular press and contemporaneous art writings, this paper explores the manner in which diplomatic aspirations and the cultural, economic, and political anxieties of U.S. elites reinforced stereotypes about Latin Americans. The fair’s cultural goods were used as props in an intentional push for improved diplomatic bonds, while the event inadvertently cast Latin America as the Other against which the U.S. expressed its own preoccupations with redefining “American” identity.